Radioactive iodine for thyrotoxicosis in childhood and adolescence: Treatment and outcomes - Sirianong Namwongprom (2018)
Objective: The aim of the present study was to evaluate the outcome of radioiodine treatment in thyrotoxicosis in childhood and adolescence. Methods: This was a retrospective study of 27 patients (ages 7.2- 19.8 years) with a diagnosis of thyrotoxicosis who received iodine-131 (I-131) treatment from January 2007 to December 2011 in the Nuclear Medicine Division, Department of Radiology, Faculty of Medicine, Chiang Mai University. Gender, duration of antithyroid drug (ATD) treatment, 24-hour I-131 uptake, thyroid weight, total dose and number of treatments with I-131, and thyroid status at 6 months after treatment were recorded. Results: The outcomes of 27 patients (85.2% female, 14.8% male) treated with radioactive iodine were analyzed to assess the effectiveness of therapy as related to dose and gland size. All children and adolescents received 150 μCi of I-131/g of thyroid tissue (n=27). Six 6 months after treatment, 44.5% of the patients were hyperthyroid, 14.8% were euthyroid, and 40.7% were hypothyroid. Of the 12 cases with hyperthyroidism, 2 cases needed a second dose of I-131 treatment, and they finally reached a hypothyroid state. The patients were classified into 2 groups according to treatment success (euthyroid and hypothyroid) and treatment failure (hyperthyroid). There were no significant differences in age, gender, duration of ATD treatment, 2- and 24-hour I-131 uptake, thyroid weight, and total I-131 dose between these two groups. Conclusions: Radioiodine treatment is safe and effective for thyrotoxicosis in childhood and adolescence. It is suitable as a good second-line therapy for patients with severe complications, those who show poor compliance, and those who fail to respond to ATD treatment. © Journal of Clinical Research in Pediatric Endocrinology, Published by Galenos Publishing.